The Damage-Associated Molecular Patterns (DAMPs) as Potential Targets to Treat Osteoarthritis: Perspectives From a Review of the Literature - Lambert, Cécile; Zappia, Jérémie; Sanchez, Christelle; Florin, Antoine; Dubuc, Jean-Emile; Henrotin, Yves (Frontiers in Medicine, 2021)
During osteoarthritis (OA) process, activation of immune systems, whether innate or adaptive, is strongly associated with low grade systemic inflammation. This process is initiated and driven in the synovial membrane, especially by synovium cells, themselves previously activated by damage-associated molecular patterns (DAMPs) released during cartilage degradation. These fragments exert their biological activities through Pattern-Recognitions Receptors (PRRs that, as a consequence, induces the activation of the signalling pathways and beyond the release of inflammatory mediators, the latter contributing to the vicious circle between cartilage and synovial membrane. The primary endpoint of this review is to provide the reader with an overview of these many molecules categorized as DAMPs and the contribution of the latter to the pathophysiology of the OA. We will also discuss the different strategies to control their effects. We are convinced that a better understanding of DAMPs, their receptors and pathological mechanisms associated represent a decisive issue for degenerative joint diseases such as OA.